2017
DOI: 10.3390/sym9050071
|View full text |Cite
|
Sign up to set email alerts
|

Lateralized Functions in the Dog Brain

Abstract: Understanding the complementary specialisation of the canine brain has been the subject of increasing scientific study over the last 10 years, chiefly due to the impact of cerebral lateralization on dog behaviour. In particular, behavioural asymmetries, which directly reflect different activation of the two sides of the dog brain, have been reported at different functional levels, including motor and sensory. The goal of this review is not only to provide a clear scenario of the experiments carried out over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 86 publications
(119 reference statements)
4
22
0
Order By: Relevance
“…It has been found, for instance, that dogs and horses perceive the content of human and conspecific emotional signals through single sensory modalities (i.e., they perceive human and conspecific emotional vocalizations [11,52,53], faces [54,55], and olfactory signals [56], see [57] for review), but also cross-modally [30,39,40], suggesting that they form a cognitive multimodal representation of other individuals' inner states. Moreover, dogs and horses show a functional understanding of human emotional signals and adjust their behavior according to the valence and intensity of the emotional message conveyed [11,[52][53][54][55][56][57][58][59]. Similar results have been recently reported by Nawroth and colleagues for goats, which discriminate human facial expression of anger and happiness and prefer to interact with the latter [60].…”
Section: Introductionsupporting
confidence: 78%
“…It has been found, for instance, that dogs and horses perceive the content of human and conspecific emotional signals through single sensory modalities (i.e., they perceive human and conspecific emotional vocalizations [11,52,53], faces [54,55], and olfactory signals [56], see [57] for review), but also cross-modally [30,39,40], suggesting that they form a cognitive multimodal representation of other individuals' inner states. Moreover, dogs and horses show a functional understanding of human emotional signals and adjust their behavior according to the valence and intensity of the emotional message conveyed [11,[52][53][54][55][56][57][58][59]. Similar results have been recently reported by Nawroth and colleagues for goats, which discriminate human facial expression of anger and happiness and prefer to interact with the latter [60].…”
Section: Introductionsupporting
confidence: 78%
“…the loudspeaker) when hearing the human voices broadcast during the negative interactions, suggesting a right hemisphere main involvement in processing such voices (80–90% of the optic fibres decussation in horses’ brain 55 ). This finding is consistent with the right hemisphere specializations for the perception and the expression of intense/negative emotions and the control of rapid responses previously described for several vertebrate species 1,56 . Specifically in horses, the right hemisphere activation has been reported in the visual analysis of potentially fear-inducing stimuli (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Neither the direction nor strength of the dogs' paw preferences differed significantly according to canine sex or castration status. Again, the literature is divided on this matter and results appear to be population-dependant [23,32,33,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…In marmosets, for example, studies showed that left-handed animals (right hemispheric dominance) were more fearful of alarm calls [40], more likely to show higher cortisol levels [41], and were less reactive to the effects of social facilitation on capturing prey [42] than right-handed marmosets (left hemispheric dominance). Thus, it could be hypothesised that animals with a left-limb bias are less likely to exploit new resources and are more likely to express negative emotional functioning compared to individuals with a right-limb bias [32]. Recent studies on marmosets [43] and dogs [44] confirmed this link by observing that a stronger left-limb motor lateralisation was associated with a more negative or 'pessimistic' cognitive bias.…”
Section: Discussionmentioning
confidence: 99%